Prediction of exocrine and endocrine insufficiency after pancreaticoduodenectomy using volumetry. Issue 4 (3rd July 2020) - Hartman, V.; Op de Beeck, B.; Chapelle, T.; Bracke, B.; Ysebaert, D.; De Block, C.; Roeyen, G.
Abstract: Objectives: The aim of this study is to evaluate the use of pancreatic volumetric assessment to predict exocrine and endocrine insufficiency after pancreaticoduodenectomy. Methods: Thirty-seven patients who underwent pancreaticoduodenectomy were included in the study. Endocrine function was assessed in all patients without a history of diabetes using an oral glucose tolerance test. A 13C-labeled mixed triglyceride (MTG) breath test evaluated exocrine function before and after resection. Volumetric measurements were performed on CT or MRI. Results: The volumetric measurements could not predict pre- or postoperative diabetes. Moreover, the resected volume was significantly lower in patients who developed diabetes after resection. Comparing patients with a normal and disturbed postoperative MTG, postoperative volumes and parenchymal thickness were significantly different. The parenchymal thickness on postoperative imaging is withheld as a predictive factor (OR = .85 [95% CI .71–1.01], p  = .049). The best cutoff value to predict exocrine insufficiency is a parenchymal thickness of less than 11.4 mm (AUC = .76, p  = .025, sensitivity = 88.9%, specificity = 70.0%). Conclusions: Pancreatic remnant volumetry and parenchymal thickness measurement after pancreaticoduodenectomy are correlated with exocrine insufficiency, but with limited predictive value. None of the preoperative measurements are withheld to predict postoperative exocrine function. Pre- and postoperative volumetry appear to have no use in predicting postoperative diabetes.